Incidence rate of postoperative cognitive dysfunction at different anesthetic depths and its correlation with serum levels of RAGE, NR2B, CREB, and NFL - Yang Xuegang; Lin Xuhe; Chen Qingjuan; Zhang Wenwen (Romanian Journal of Laboratory Medicine)
Anesthetic depth may affect cognitive function, which is reflected by serum biomarker levels. We aimed to investigate the incidence rate of postoperative cognitive dysfunction (POCD) at different anesthetic depths and its correlations with levels of serum receptor for advanced glycation end product (RAGE), N-methyl-D-aspartate receptor 2B subunit (NR2B), cAMP response element-binding protein (CREB) and neurofilament light chain (NFL).